The potential therapeutic role of extracellular vesicles in critical-size bone defects: Spring of cell-free regenerative medicine is coming - Liu, Fen; Sun, Tianyu; An, Ying; Ming, Leiguo; Li, Yinghui; Zhou, Zhifei; Shang, Fengqing (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the incidence of critical-size bone defects has significantly increased. Critical-size bone defects seriously affect patients’ motor functions and quality of life and increase the need for additional clinical treatments. Bone tissue engineering (BTE) has made great progress in repairing critical-size bone defects. As one of the main components of bone tissue engineering, stem cell-based therapy is considered a potential effective strategy to regenerate bone tissues. However, there are some disadvantages including phenotypic changes, immune rejection, potential tumorigenicity, low homing efficiency and cell survival rate that restrict its wider clinical applications. Evidence has shown that the positive biological effects of stem cells on tissue repair are largely mediated through paracrine action by nanostructured extracellular vesicles (EVs), which may overcome the limitations of traditional stem cell-based treatments. In addition to stem cell-derived extracellular vesicles, the potential therapeutic roles of nonstem cell-derived extracellular vesicles in critical-size bone defect repair have also attracted attention from scholars in recent years. Currently, the development of extracellular vesicles-mediated cell-free regenerative medicine is still in the preliminary stage, and the specific mechanisms remain elusive. Herein, the authors first review the research progress and possible mechanisms of extracellular vesicles combined with bone tissue engineering scaffolds to promote bone regeneration via bioactive molecules. Engineering modified extracellular vesicles is an emerging component of bone tissue engineering and its main progression and clinical applications will be discussed. Finally, future perspectives and challenges of developing extracellular vesicle-based regenerative medicine will be given. This review may provide a theoretical basis for the future development of extracellular vesicle-based biomedicine and provide clinical references for promoting the repair of critical-size bone defects.